Subconcussive brain vital signs changes predict head-impact exposure in ice hockey players. Issue 2 (6th April 2021) - Fickling, Shaun D; Smith, Aynsley M; Stuart, Michael J; Dodick, David W; Farrell, Kyle; Pender, Sara C; D'Arcy, Ryan C N
Abstract: The brain vital signs framework is a portable, objective, neurophysiological evaluation of brain function at point-of-care. We investigated brain vital signs at pre- and post-season for age 14 or under (Bantam) and age 16–20 (Junior-A) male ice hockey players to (i) further investigate previously published brain vital sign results showing subconcussive cognitive deficits and (ii) validate these findings through comparison with head-impact data obtained from instrumented accelerometers. With a longitudinal study design, 23 male ice hockey players in Bantam ( n = 13; age 13.63 ± 0.62) and Tier II Junior-A ( n = 10; age 18.62 ± 0.86) divisions were assessed at pre- and post-season. None were diagnosed with a concussion during the season. Cognitive evoked potential measures of Auditory sensation (N100), Basic attention (P300) and Cognitive processing (N400) were analysed as changes in peak amplitudes and latencies (six standard scores total). A regression analysis examined the relationship between brain vital signs and the number of head impacts received during the study season. Significant pre/post differences in brain vital signs were detected for both groups. Bantam and Junior-A players also differed in number of head impacts (Bantam: 32.92 ± 17.68; Junior-A: 195.00 ± 61.08; P < 0.001). Importantly, the regression model demonstrated a significant linear relationship between changes in brain vital signs and total head impacts received ( R = 0.799, P = 0.007), with clear differences between the Bantam and Junior-A groups. In the absence of a clinically diagnosed concussion, the brain vital sign changes appear to have demonstrated the compounding effects of repetitive subconcussive impacts. The findings underscored the importance of an objective physiological measure of brain function along the spectrum of concussive impacts. Abstract : The brain vital signs framework is a portable, neurophysiological evaluation of brain function. Fickling et al. observed a strong, significant linear relationship between changes in brain vital signs and the total number of subconcussive head impacts sustained over the course of a playing season in male ice hockey players. Graphical Abstract: